2019
DOI: 10.1186/s12985-019-1247-0
|View full text |Cite
|
Sign up to set email alerts
|

A novel avian isolate of hepatitis E virus from Pakistan

Abstract: BackgroundAvian hepatitis E virus (aHEV) has been associated with hepatitis-splenomegaly syndrome (HSS) in chickens along with asymptomatic subclinical infection in many cases. So far, four genotypes have been described, which cause infection in chickens, specifically in broiler breeders and layer chickens. In the present study, we isolated and identified two novel aHEV strains from the bile of layer chickens in Pakistan evincing clinical symptoms related to HSS.MethodologyHistology of liver and spleen tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Different genotypes of avian HEV have been reported worldwide [10,20,21,22]. Zhao et al reported the complete genome sequence of the rst avian HEV in 2010 [3], since then, the avian HEV isolates of different genotypes have been widely reported in China, including Shandong, Jiangxi and Guangdong provinces [10,13,23].…”
Section: Discussionmentioning
confidence: 99%
“…Different genotypes of avian HEV have been reported worldwide [10,20,21,22]. Zhao et al reported the complete genome sequence of the rst avian HEV in 2010 [3], since then, the avian HEV isolates of different genotypes have been widely reported in China, including Shandong, Jiangxi and Guangdong provinces [10,13,23].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the first sequenced strain of avian HEV was isolated from chickens with hepatitis-splenomegaly syndrome in the United States in 2000 ( Haqshenas et al., 2001 ). After that, avian HEV strains were successively reported in Europe ( Bilic et al., 2009 ); Shandong, China ( Zhao et al., 2010 ); Hungary ( Bányai et al., 2012 ); South Korea ( Kwon et al., 2012 ); Taiwan, China ( Hsu and Tsai, 2014 ); Guangdong, China ( Zhang et al., 2019 ); and Pakistan ( Iqbal et al., 2019 ), which confirmed again the high diversity of the avian HEV and the existence of difierent genotypes ( Bányai et al., 2012 ; Sprygin et al., 2012 ; Sun et al., 2019 ), indicating that more different types of strains may be found in the future. In this study, to further clarify the molecular characteristics of the avian HEV strain circulating in the aforementioned farm, the capsid gene of the virus was sequenced using the Sanger method.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was extracted from the liver and feces using a total RNA extraction kit (Axygen, USA). The extracted RNA was reverse transcribed into cDNA using the cDNA Reverse Transcription Kit (Takara, Dalian, China) and then PCR detection with two sets of primers ( Supplementary Table 1 ) targeting the partial ORF2 capsid gene sequences of avian HEV was performed ( 12 , 18 ). At the same time, total DNA was extracted from the liver tissue using the DNA extraction kit (TianGen, China), and the PCR detections for avian leukosis virus (ALV), Marek's disease virus (MDV), reticuloendotheliosis virus (REV), and fowl adenovirus serotype 4 (FAdV-4) were also performed, respectively, by using the primers ( Supplementary Table 2 ) as our previous reports ( 19 ).…”
Section: Methodsmentioning
confidence: 99%